A Chiemgauer, mint sikeres helyi pénz működése - Varga, József (Közép-Európai Közlemények, 2017)
The paper analyses one of the local currencies’ issue and operation, the successful Chiemgauer in South Germany. During the analysis it was important that the Chiemgauer was established with a non-profit aim, for supporting education and research. Accordingly the voucher system issuing organization was founded as a non-profit organization The basic objective of the initiative was to create an educational area by the established projects (such as student companies, conferences, trainings, professional consultations and meetings), which area can contribute to the sustainable development of the region. The concept of sustainability refers to the importance of the environmental, economic and social aspects at the same time. The initiative started in 2003 have become dominant in the Chiemsee area after several attempts. Based on the idea of Christian Gelleri and Thomas Mayer the initiative was created by six students and nowadays it has thousands of users. The study analyses the results of the Chiemgauer. The local currency compared to the initial issuance achieved a huge turnover increase within a decade: the turnover in Chiemgauer increased nearly a hundredfold. Another important results is that the initial 90% of downshift decreased to 29% so the Chiemgauer has become a real local currency, it rotates mostly among the participants of the system. If we add to this the initially higher and increasing rotation speed, a successful picture becomes complete.